The effect of a holistic nurse coaching intervention on glycemic control, diabetes self-management, and empowerment: a randomized controlled trial - Tuğba Bilgehan; Bahar Vardar İnkaya (BMC Nursing)
Strengths of the Research This is the first randomized controlled study in Türkiye in which holistic nurse coaching was offered to individuals with diabetes. The presence of two interventions and a control group in the study makes the study powerful. The researchers spent 54 h on diabetes education and 306 h on the holistic nurse coaching interviews.